Determinación de la oferta hídrica de las microcuencas de los ríos Ishpi, Daldal, Uldán y quebrada Cachipata, en la provincia de Chimborazo - Jaya Jaya, Vanessa del Pilar (2023)
The micro basins of the Ishpi, Daldal, Uldán, and Cachipata streams are located in the sub- basin of the Chambo River, in the Chambo canton and southeast of Riobamba canton. The micro-watersheds play an essential role in the hydrological cycle of the sector, as they are located in a place of high agricultural and livestock demand, so it is essential to know the flow information so that irrigation projects can be carried out in the best possible way. There are no studies on water supply and demand since the micro basins do not have hydrological stations that measure flows in real-time. Therefore, this lack of observed hydrometeorological data makes it necessary to use hydrological models to obtain mathematical approximations to know the amount of water offered by this area of the Chambo River sub-basin, allowing the design of sustainable and sustainable projects that do not affect the flow of these basins. The purpose of this research is to determine the water supply for the Ishpi, Daldal, Uldán, and Cachipata creek micro-basins, using the precipitation-runoff method, as well as field capacity analysis and the geomorphology of the micro-basins, for which sampling points were established in strategic locations depending on the vegetation cover and soil taxonomy using GIS. The analysis of hydraulic parameters indicated percentages of porosity, organic matter, permeability coefficient, infiltration capacity, and the texture of 5 vegetation covers (moorland, grassland, herbaceous-bushy vegetation, and crop). According to the results, it is evident that soil erosion is due to anthropic activities in the area, mainly the advance of the agricultural frontier and overgrazing. Once the described parameters were obtained, we proceeded to the mathematical modeling in the HEC-HMS program, applying the SCS curve number method, using daily precipitation data, monthly average evapotranspiration, daily temperatures, as well as geomorphological results such as runoff threshold, delay time and curve number, over 20 years, obtaining daily flow values from 1981-2021. After the rainfall-runoff model, the Ishpi, Daldal, Uldán, and Cachipata micro basin values are 0,382 m3/s, 0.68 m3/s, 1,044 m3/s, and 0,276 m3/s, respectively. The water supply of the micro-basins offers the possibility that part of its flow can be used to meet the population's needs, provided that the resource is used appropriately.